Novel bean varieties reach millions of African farmers - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2010)
This work takes place through the national Research and Development R&D programs that make up the Pan-Africa Bean Research Alliance (PABRA). The alliance encompasses the Eastern and Central Africa Bean Research Network (ECABREN), the Southern Africa Bean Research Network (SABRN), and the West and Central Africa Bean Research Network (WECABREN). Mrs. Aidah Abia, Chairperson of Balla Women and Youth Bean Seed Producers in northern Uganda, testifies that growing beans for seed has changed her life. She emphasized that her income increased from the sale of beans allowing her to send children to school, meet medical expenses, and purchase household items such as paraffin and soap. Common beans (Phaseolus vulgaris L.) are an important crop for food, cash, and agroecosystems improvement in many countries in eastern, central, and southern Africa. The crop is mainly grown by small-scale farmers with limited access to agricultural inputs.